Time Series Trend Analysis of the Effect of Rainfall on the Productivity of Cayenne Pepper (Capsicum frutescens L.) in Southeast Sulawesi Province - Indriyana; Sitti Aida Adha Taridala; Wa Ode Yusria (International Journal of Technology and Education Research, 2025)
Climate change occurs due to changes in climate elements such as wind, air humidity, temperature and rainfall. Climate change is caused by natural events and human activities, which threaten the agricultural sector and food security, impacting humans and crops. The affected agricultural sector, including the horticulture subsector, experienced a decline in production and farmer income. One of the affected horticultural commodities is cayenne pepper (Capsicum frutescens L.), which is important for fulfilling people's nutrition. This research aims to: (1) Find out the productivity of cayenne pepper in Southeast Sulawesi Province, and (2) Analyze the effect of rainfall on the productivity of cayenne pepper in Southeast Sulawesi Province. The data used in this research is secondary data, obtained from the Southeast Sulawesi Provincial Plantation and Horticulture Service and the Southeast Sulawesi Central Statistics Agency (BPS). The data in this study were analyzed using simple regression. The research results show that the productivity of cayenne pepper in Southeast Sulawesi Province from 1993-2023 is 29,784 Ku/Ha, varying from year to year. The estimation results of the regression equation model show that rainfall has no effect on cayenne pepper productivity